The additive effects of hydroxychloroquine to maintenance therapy with standard of care in patients with systemic lupus erythematosus. (5th February 2020) - Miyagawa, Ippei; Nakano, Kazuhisa; Nakayamada, Shingo; Iwata, Shigeru; Hanami, Kentaro; Fukuyo, Shunsuke; Kubo, Satoshi; Kawabe, Akio; Miyazaki, Yusuke; Inoue, Yoshino; Ueno, Masanobu; Ohkubo, Naoaki; et al.
Abstract: Aim: In this retrospective study, the effect of hydroxychloroquine (HCQ) added to maintenance therapy according to the standard of care (SoC) was evaluated for 1 year in 101 patients with systemic lupus erythematosus (SLE). Methods: The primary endpoint was the SLE Disease Activity Index (SLEDAI). The secondary endpoints were the British Isles Lupus Assessment Group index, serum complement activity (CH50) levels, anti‐double‐stranded DNA (dsDNA) antibody titer, concomitant corticosteroid (CS) dose, and Systemic Lupus International Collaborating Clinics (SLICC) damage index. These variables were compared between the SoC + HCQ (n = 42) and SoC (n = 59) groups. Results: The SLEDAI improved from 2 (0, 6) to 0 (0, 4) in the SoC + HCQ group ( P = .038) but significantly deteriorated from 1 (0, 4) to 2 (0, 8) in the SoC group ( P = .033). CH50, anti‐dsDNA antibody titer, concomitant CS dose, and SLICC damage index did not significantly change. The increase in the SLEDAI and concomitant CS dose after 1 year were all significantly greater in the SoC group, and the proportion of patients with SLEDAI flare was significantly lower in the SoC + HCQ group (SoC + HCQ: 4.76% vs SoC: 25.4%, P  = .006). Univariate logistic regression analyses identified HCQ as a predictive factor for no SLEDAI flare ( P  = .003, odds ratio 6.81, 95% confidence interval 1.77‐45.00). Conclusions: The use of HCQ effectively improved SLEDAI scores and was a predictive factor for the prevention of SLEDAI flare. Therefore, HCQ may be considered a potential mainstay of maintenance therapy.